(untitled) (Bangladesh Pharmaceutical Journal, 2017)
The objective of this study was to analysis in vitro release kinetics of Azithromycin from bi-layer tablets prepared by direct compression using high viscosity to low viscosity grades of hydroxypropyl methyl cellulose (HPMC K15M, HPMC K4M, HPMC 50 cps), Carbopol 934p and Carbopol 974p. In addition, it also includes evaluating the effect of formulation variables like polymer proportion and polymer viscosity on the release of Azithromycin. In vitro release studies were performed using USP Type-II (Rotating paddle method) at 100 rpm. The dissolution medium consisted of 0.1N HCl (900 ml) for the first 2 hr and the phosphate buffer (pH 6.0) from 3rd to 10th hour. From twenty five different formulations (F-1 to F-25) based on polymer variation, model-dependent and independent methods were used for data analysis and the best results were observed for HPMC 50cps in Korsmeyer- Peppas (R2=0.995 on F-23) kinetic model. The release mechanism of all formulations was Fickian. Bangladesh Pharmaceutical Journal 20(1): 54-63, 2017